2007
DOI: 10.1089/pho.2007.2041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Level Laser and Plyometric Exercises in the Treatment of Lateral Epicondylitis

Abstract: The results suggested that the combination of laser with plyometric exercises was more effective treatment than placebo laser with the same plyometric exercises at the end of the treatment as well as at the follow-up. Future studies are needed to establish the relative and absolute effectiveness of the above protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
85
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(96 citation statements)
references
References 40 publications
3
85
0
4
Order By: Relevance
“…Future studies should be conducted using ultrasound and eccentric training in the management of LET, in order to find out whether the combination of the two treatments is more effective than the eccentric training alone in the management of LET. Similar studies have been conducted for other physical modalities such as low level laser therapy [39]. These studies showed that using a therapeutic modality with eccentric training, patients with LET managed quicker.…”
Section: Limitationssupporting
confidence: 59%
“…Future studies should be conducted using ultrasound and eccentric training in the management of LET, in order to find out whether the combination of the two treatments is more effective than the eccentric training alone in the management of LET. Similar studies have been conducted for other physical modalities such as low level laser therapy [39]. These studies showed that using a therapeutic modality with eccentric training, patients with LET managed quicker.…”
Section: Limitationssupporting
confidence: 59%
“…We identified one relevant RCT not currently included in a systematic review; 186 this was a placebo-controlled study and had a sample size of 47 participants, thus, on its own, it may have limited impact on the existing recommendations regarding this intervention. 156,158,186 In addition, we identified three RCTs included in intermediate-/low-quality reviews. 153,156,158 As there is insufficient evidence to demonstrate either benefit or lack of effect of laser for LET, and given there are recent RCTs (2003-13) we recommend that an updated systematic review may be of benefit.…”
Section: Laser Therapymentioning
confidence: 99%
“…156,158,186 In addition, we identified three RCTs included in intermediate-/low-quality reviews. 153,156,158 As there is insufficient evidence to demonstrate either benefit or lack of effect of laser for LET, and given there are recent RCTs (2003-13) we recommend that an updated systematic review may be of benefit. However, some consideration should also be given to conducting good-quality RCTs.…”
Section: Laser Therapymentioning
confidence: 99%
“…However, there is still no approved evidence-based treatment method for lateral epicondylitis [3,5,15]. One of the widely-suggested treatments which has been used in past two decades leading to reduce pain in musculoskeletal disorders with various etiologies is Low Level Laser Therapy (LLLT) [16]. Physiotherapists apply the LLLTs in different cases such as carpal tunnel syndrome, joint disorders, tendinopathy, medial/lateral epicondylitis, osteoarthritis, back pain, ankle sprains, venous ulcers, and diabetes [16].…”
Section: Introductionmentioning
confidence: 99%
“…One of the widely-suggested treatments which has been used in past two decades leading to reduce pain in musculoskeletal disorders with various etiologies is Low Level Laser Therapy (LLLT) [16]. Physiotherapists apply the LLLTs in different cases such as carpal tunnel syndrome, joint disorders, tendinopathy, medial/lateral epicondylitis, osteoarthritis, back pain, ankle sprains, venous ulcers, and diabetes [16]. Low level or cold laser therapy with a wavelength of 904 nm has less than 500 mW power and high level laser with similar wavelength has a power higher than 500 mW.…”
Section: Introductionmentioning
confidence: 99%